2021
DOI: 10.1097/j.pain.0000000000002540
|View full text |Cite
|
Sign up to set email alerts
|

Unique considerations for exercise programs to prevent future low back pain: the patient perspective

Abstract: Supplemental Digital Content is Available in the Text. Patients want highly individualised exercise programs for low back pain prevention that provide meaningful explanations of exercises and help them maintain exercise in the long-term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Most of the time, progress took the form of an improvement in shoulder strength or the experience of less shoulder pain with a particular movement, which aligns with previous qualitative research in the area of non-specific low back pain. 41 Similar to the work of Littlewood et al, 20 a lack of timely symptom improvement was met with suspicion and doubt about the benefit of a particular exercise program, which affected motivation and adherence to the exercise program, ultimately leading to poor clinical outcomes. The recovery from RCRSP with exercise is not usually a quick process, and in some cases, it is recommended that 12 months of exercise therapy be trialed prior to escalating treatment to more invasive treatments 45 ; the desire for a timely improvement in shoulder symptoms by patients with exercise may prove difficult.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Most of the time, progress took the form of an improvement in shoulder strength or the experience of less shoulder pain with a particular movement, which aligns with previous qualitative research in the area of non-specific low back pain. 41 Similar to the work of Littlewood et al, 20 a lack of timely symptom improvement was met with suspicion and doubt about the benefit of a particular exercise program, which affected motivation and adherence to the exercise program, ultimately leading to poor clinical outcomes. The recovery from RCRSP with exercise is not usually a quick process, and in some cases, it is recommended that 12 months of exercise therapy be trialed prior to escalating treatment to more invasive treatments 45 ; the desire for a timely improvement in shoulder symptoms by patients with exercise may prove difficult.…”
Section: Discussionmentioning
confidence: 89%
“…A desire for individualized exercise prescription reported in this study is similar to the previous qualitative research evidence for PFP and non-specific low back pain. 33 , 41 The desire for a tailored approach to exercise prescription for RCRSP is supported by empirical data which suggest there is no universal best exercise approach. 42–44 Therefore, rather than decreeing 1 particular exercise approach as superior, clinicians should endeavor to construct an exercise program in close collaboration with the individual in question and with careful consideration of access to equipment, past experiences with exercise, beliefs about exercise, and their individual goals.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the education sector in collaboration with the health sector should design regular physical activity programmes to improve the health of the teachers. Different guidelines for the prevention and management of LBP also emphasised the importance of regular physical activity and exercise 52…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Interestingly, individuals with LBP may feel uncertain about exercise. Qualitative research has suggested that although people with LBP often believe that exercise can prevent or reduce future LBP, some experience uncertainty about undertaking exercise that is unfamiliar 1 or exercising while in pain. 14 Although the uncertainties surrounding diagnosis, prognosis, and management have been discussed in the LBP literature, the uncertainty clinicians experience when working with individuals with LBP is not limited to these biomedical aspects.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Interestingly, individuals with LBP may feel uncertain about exercise. Qualitative research has suggested that although people with LBP often believe that exercise can prevent or reduce future LBP, some experience uncertainty about undertaking exercise that is unfamiliar 1 or exercising while in pain. 14…”
Section: Introductionmentioning
confidence: 99%